VALIDITY OF TWO HOURS ORAL GLUCOSE TOLERANCE TEST AT 48-72 HOURS AFTER DELIVERY IN DETERMINING THE DEVEL- OPMENT OF TYPE 2 DIABETES AT SIX WEEKS POSTPARTUM IN PATIENTS WITH GESTATIONAL DIABETES MELLITUS - Bhalli, Amanullah; Sukhan, Shereen; Safeer, Khushbakht; Ahmad Khan, Khurshid; Rasheed, Aqeela; Mushtaq, Samsam; Ahmad Khan, Zohaib (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the validity of 2-hours oral glucose tolerance test (OGTT) conducted 48-72 hours after delivery in determining the development of type 2 diabetes at six weeks postpartum in patients with gestational diabetes mellitus (GDM). Methodology: This was a prospective, cohort study conducted at Jinnah Alla- ma Iqbal Institute of Diabetes & Endocrinology (JAIDE), Medical Unit-4, Jinnah Hospital, Lahore, from February, 2017 to July, 2017. Women diagnosed with GDM at 24-28 weeks of gestation using 75 grams OGTT were recruited in the study. The study outcomes were the calculation of sensitivity, specificity, and predictive values (positive and negative) of the 2 days postpartum OGTT results to predict diabetes mellitus and impaired glucose tolerance. Results: The study was conducted on 138 female patients with mean age 28.6 ±9.2 years (range: 17–38 years). The mean fasting blood glucose level 48 hours and six weeks after delivery was 98.7 mg/dl and 86.6 mg/dl respectively (p <0.001). The frequency of diabetes was found out to be 4.3% and 9.4% at 48 hours and 6 weeks postpartum respectively. The sensitivity, specificity, positive predictive value and negative predictive value of OGTT conducted at 48-72 hours postpartum for diagnosis of diabetes mellitus was found out to be 76.2%, 96.1%, 67.4% and 94.1% respectively. Conclusion: Oral glucose tolerance test performed 48-72 hours postpartum is a useful tool to predict diabetes mellitus in women with GDM. It is helpful in identifying those women who need further monitoring and testing for type 2 diabetes.